GM‐CSF reduces amylin amyloid and prevents pancreatic cell death in the hIAPP mouse model of Type 2 diabetes mellitus, a known risk factor for Alzheimer's disease. (20th December 2022) - Wang, Athena Ching‐Jung; Boyd, Timothy D.; Markham, Neil; Adame, Vanesa; Potter, Huntington
Abstract: Background: People with Type II diabetes mellitus (T2D) are at higher risk for developing Alzheimer's disease (AD). T2D is characterized histopathologically by the accumulation of fibrillary amyloid deposits in the pancreas, which are comprised primarily of human islet amyloid polypeptide (hIAPP), also known as amylin. Amylin, which self‐aggregates in a manner similar to amyloid beta, has been implicated as a source of pathogenesis in both T2D and AD. In T2D patients, pancreatic amyloid deposition occurs before and induces islet β‐cell apoptosis. Granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) has demonstrated anti‐apoptotic, neuroprotective, neurotrophic, immunomodulatory, and regenerative effects in several neuronal injury models. We discovered that GM‐CSF treatment rapidly reduced cerebral amyloidosis and reversed cognitive impairment in transgenic AD models (Boyd et al, 2010), which led to the initiation and successful completion of a Phase 2 clinical trial (NCT01409915) using sargramostim (rhuGM‐CSF) in mild‐to‐moderate AD participants (Potter et al., 2021). Thus, we hypothesized the GM‐CSF might also reduce amyloid and prevent cell death in the pancreas of the hIAPP mouse model of T2D. Method: We investigated GM‐CSF treatment effects in 12‐week‐old male hemizygous hIAPP mice (Jackson strain Tg(Ins2‐IAPP)RHFSoel), which accumulate amylin amyloid in pancreatic islets. Mice received daily subcutaneous injections (5 days/week for 23 total injections) of either recombinant murine GM‐CSF (5 µg/day or ∼167 µg/kg; n=9) or sterile saline (n=7), and the animals were then euthanized, perfused according to CU Anschutz OLAR regulations, and pancreatic tissues were obtained and processed for histopathology. Whole blood samples were obtained before perfusion, and blood chemistry analyses were performed for T2D biomarker levels (BUN, amylase, LDH, glucose, ALT). Unpaired t‐tests were used to determine significant differences (p<0.05) between treatment groups. Result: Thioflavin‐S staining revealed significantly less pancreatic amyloid (p=0.00114, saline n=3, GM‐CSF n=7) and Caspase‐3 immunohistochemistry showed significantly less apoptosis (p=0.0057, Saline n=7, GM‐CSF n=9) in pancreatic tissue from the GM‐CSF‐treated group. There were no significant differences observed for the blood chemistry biomarkers, but trends were observed for lower levels of BUN and higher levels of amylase in the GM‐CSF‐treated group. Conclusion: These preliminary data suggest a therapeutic potential for GM‐CSF to prevent or treat T2D, and thereby reduce AD risk.